2013
DOI: 10.1371/journal.pgen.1003865
|View full text |Cite|
|
Sign up to set email alerts
|

A Minimal Nitrogen Fixation Gene Cluster from Paenibacillus sp. WLY78 Enables Expression of Active Nitrogenase in Escherichia coli

Abstract: Most biological nitrogen fixation is catalyzed by molybdenum-dependent nitrogenase, an enzyme complex comprising two component proteins that contains three different metalloclusters. Diazotrophs contain a common core of nitrogen fixation nif genes that encode the structural subunits of the enzyme and components required to synthesize the metalloclusters. However, the complement of nif genes required to enable diazotrophic growth varies significantly amongst nitrogen fixing bacteria and archaea. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(177 citation statements)
references
References 48 publications
5
171
0
1
Order By: Relevance
“…Previous reports have suggested that expression levels of nifD and nifK genes could be used as indicators of SNF capacity (9,(16)(17)(18). The higher levels of nifD and nifK expression under Pisufficient conditions observed in MmSWRI9-induced nodules relative to McCP-31-induced nodules suggest that the MmSWRI9-inoculated association may have higher SNF capacity than the McCP-31-inoculated association under Pi-sufficient conditions (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous reports have suggested that expression levels of nifD and nifK genes could be used as indicators of SNF capacity (9,(16)(17)(18). The higher levels of nifD and nifK expression under Pisufficient conditions observed in MmSWRI9-induced nodules relative to McCP-31-induced nodules suggest that the MmSWRI9-inoculated association may have higher SNF capacity than the McCP-31-inoculated association under Pi-sufficient conditions (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…SNF capability of leguminous plants is controlled by the rhizobial nitrogenase complex, which catalyzes the reduction of N 2 into ammonia (15). The nifDK genes are the structural genes encoding the MoFe protein subunits of the nitrogenase complex, and assessing their expression levels has been shown to be a reliable method for evaluating the contribution of the N 2 fixing bacteria to plant N nutrition (9,(16)(17)(18). Thus, analysis of the expression levels of the nifDK genes will enable us to characterize the SNF capacity of the nodules induced by the tested strains under both normal and low Pi conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that an operon comprising nine genes derived from Paenibacillus sp. WLY78 is sufficient to express active molybdenum nitrogenase in E. coli (20). However, the minimal FeFe nitrogenase system described here has certain advantages, notably the simpler mode of FeFe-co biosynthesis and, in particular, the absence of a requirement for Mo, because this element is most probably limiting in plant organelles that lack molybdoenzymes.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have established that Escherichia coli can provide a useful host for engineering diazotrophy (17)(18)(19), determining the minimum requirements for nitrogen fixation in evolutionary distant diazotrophs (20), and redesigning nif gene clusters for synthetic biology (21,22). Recently, we developed a modular operon-based system for functional analysis of the Klebsiella oxytoca nif gene cluster in E. coli (21).…”
Section: Significancementioning
confidence: 99%
“…are mentioned to be involved in nitrogen fixation. These will be an important step, of long-standing interest, for developing biofertilizers that can help non-legume crops to "fix" nitrogen at the same time with maintaining growth yields [14]. Phosphate solubilization is another highly important tool in plant growth promotion.…”
Section: IIImentioning
confidence: 99%